Standardized Concept Design of Structural Testing and Camber of Railway Flat Wagons - hary soebagyo; Arief Riyadi T. K (Teknobiz : Jurnal Ilmiah Program Studi Magister Teknik Mesin, 2026)
The train is a means of mass transportation that functions to transport people and goods. The level of train safety must be maintained during operation, especially the structural parts which must be strong and reliable in accepting the loads they carry following RAMS provisions (Reliability, Availability, Maintainability, Safety). The main structural part of concern is the lower frame of the train carriage whose main function is to support all the loads received. The design of the lower frame structure is made in such a way that it is slightly curved so that there is a pre-stress load that can withstand bending loads when the structure is loaded. This slightly curved structural design is called "camber" where camber is defined as the lowest distance between the midpoint of the span of the carriage structure and the fulcrum. Considering the importance of flat carriage structures and their camber, it is necessary to create standard structural testing and camber measurement standards for the railway industry in Indonesia. This paper discusses how to develop standard concepts for testing methods and measuring camber values ​​which refer to international standards and applicable laws and regulations in Indonesia. The results of this study are in the form of a design concept containing methods and stages for testing of the lower frame structures and measuring the camber of the lower frame structures of the train. This concept can be used as initial material for developing national standards in the manufacture of the lower frame structure of the train.